Carbon trends (Elsevier Ltd, 2020)
"Carbon Trends is an international, peer-reviewed, open-access journal, and a companion title to the well-established journal, Carbon. This journal offers an open access platform to communicate progress in the field of carbon materials science. The scope of Carbon Trends comprises new developments associated to all forms of carbon, including traditionally bulk carbons to low-dimensional carbon-based structures. New and significant results related to the properties of material systems where carbon plays the central role are the core of the journal. However, articles on composites and on materials closely related to carbon (e.g., similar composition or morphologies) will also be considered by the Editors of Carbon Trends. This includes nitrides, carbides, and graphene-like low-dimensional materials (0D, 1D, and 2D)."--Publisher
Keywords: Carbon : Periodicals; Carbon composites : Periodicals; Carbon; Carbon composites